Estratégias para a escrita do gênero artigo de opinião na escola: uma proposta metodológica - Costa, Karine de Oliveira (2018)
Strategies for writing genre opinion piece in school: a methodological proposal is the result of a pedagogical intervention performed in a class of ninth grade of elementary school II of a large public high school in the city of Feira de Santana-Bahia. Research-intervention had a qualitative methodological approach and theoretical framework based on Textual Linguistics. Part of the theoretical framework of base: Antunes(2016, 2009, 2003), Beth Marcuschi (2010),Geraldi (2002, 1997, 1991), Kato (2003), Koch (2016,2002),Marcuschi (2003), Passarelli (2012,2004), PCN (1998), Rodrigues (2000); among others. From a work plan, consisting of additional steps, we develop actions in the classroom, which sought to improve some skills writers of the students. We promote the systematic teaching of a text argumentative, opinion piece, contemplating the underlying writing process steps, which are: planning, writing the first version, revision and rewriting of a text. To this end, we offer 14 thematic workshops focused reading and rereading of texts, the study of linguistic and discursive aspects of the genre, writing and rewriting of an article. The texts were monitored along the search to identify the main difficulties presented by students in relation to the writing of the genre and, also, to evaluate if those difficulties were minimized from the activities developed in class. We, with research, verify that the teaching of writing of a particular genre is most effective when it occurs within an international perspective, contextualized and procedure. In the end, compare the first version of the articles with the rewritten version, whose results showed that after implementation of the activities there was improved performance of students in writing, especially in respect to textual coherence in the title role, in thematic continuity and general sense of the text